(untitled) (Al-Academy, 2023)
The research tagged (Digital Collage in Contemporary Art) consisted of four chapters. The first chapter was devoted to the methodological framework of the research. The problem ended with the following questions: How does digital collage represent contemporary art? What is the variable at the level of meaning shifts in composing works according to the digital collage? Was the digital collage a qualitative leap in the path of the aesthetic pattern in art? How does digital collage interfere with contemporary life and societies? It included the aim of the research and its importance, while the second chapter dealt with two topics, the first (reading in the concept of collage), and the second (digital collage). The third chapter was devoted to the research procedures, and the researcher chose (3) models related to the art of digital collage. The analysis was done based on the descriptive method. As for the fourth chapter, it was devoted to the results of the research and its conclusions, including: 1- The artist’s quest for experimentation to create a distinct expectation to deal with different ideas to change the style of the image to be part of the requirements of the era. 2- Benefiting from the scientific and technical transformations in the modern world led to employing the art of digital coiiage.the research ended with recommendations, proposals and alist of sources.